Pengembangan ide inovasi mochi berisi brownies dengan menggunakan proses design thinking - Gracia, Nicole; Wijayanto Aripradono, Heru (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The dessert industry faces the ongoing challenge of innovation, where existing products often share similarities in taste and presentation. This study aims to develop an innovative dessert product by combining mochi and brownies, using the Design Thinking approach. The approach involves five main stages: Empathize, Define, Ideate, Prototype, and Test. The process begins with observation and interviews to understand consumer needs and preferences. Based on initial findings, creative ideas were developed to create a unique dessert product, Mochi Brownies or